Reconstructing the Role of Parents in Shaping the Personality of the Child - Purniasih Purniasih; Sandy Ariawan (EXOUSIA : Jurnal Pendidikan Agama Kristen, 2022)
The child's personality becomes something sad to discuss. Many families have accused the world of education of failing to carry out its mandate during the Covid-19 pandemic, while the education community does not necessarily want to be blamed and blames the family because during the pandemic the children's daily lives are actually spent in the middle of the family. With regard to spirituality, families are unwittingly faced with the problem of parents' lack of motivation in encouraging children to attend Sunday School services. This study aims to reconstruct the role of parents in shaping children's personalities through Sunday School worship. This research uses qualitative methods with a narrative study approach. Researchers conducted interviews with seven informants consisting of five Sunday School teachers, four of whom were parents and two parents of Sunday School children. Based on the collection of existing data, information and facts, researchers found that: Parents only give forms of motivation externally, have not given children motivation internally. The form of external motivation givenis to give encouragement/encouragement to the child, reprimand and advise when the child makes a mistake, and encourage the child to understand his talents and interests. Internal motivation is very necessary because it can be an encouragement from within the child himself, and it needs to be built by parents to the child from childhood. Furthermore, parents shouldbe an example for their children. From field research, most parents have tried to be role models in order to motivate children to come to Sunday School. The arrangement that can be given is to be able to equip parents through seminars, workshops, and discipleship to provide knowledge on how to be the right motivator for children, so that children's personalities can be formed from an early age. In addition, parents can also accustom children to time discipline from an early age.